Gaming the system: An investigation of small business owners' attitudes to tax avoidance, tax planning, and tax evasion - Diana Onu; Lynne Oats; Erich Kirchler; Andre Julian Hartmann (Games, 2019)
To a large extent, the body of research that looks at individuals' compliance with the law focuses on the dichotomy between compliance as rule-following and noncompliance as rule-breaking. However, a fascinating case of noncompliance is that where individuals selectively follow existing rules in order to circumvent the legal principle, this behaviour has been termed "creative compliance" In the current study, we investigated the psychological underpinnings of "creative compliance" by assessing the attitudes of tax avoidance (significant minimisation of tax liability perceived to be legal) and tax evasion (illegal tax minimisation) of 330 owners of small businesses. We found that tax avoidance and tax evasion were perceived as qualitatively distinct by respondents and that they were predicted by different factors. While both tax avoidance and tax evasion were associated with weak personal norms to contribute to the tax system, tax avoidance was associated with a perception that the tax system is unfair, and that tax law has "loopholes" that can be exploited, while tax evasion was predicted by the perception that evasion is a trivial crime. Overall, we provide insight into the under-investigated behaviour of "creative compliance" and propose future research directions.
Keywords: 330; creative compliance; tax avoidance; tax compliance; tax evasion; tax planning